2013
DOI: 10.1371/journal.pone.0064622
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tuberculosis Drug Induced Hepatotoxicity among TB/HIV Co-Infected Patients at Jimma University Hospital, Ethiopia: Nested Case-Control Study

Abstract: BackgroundThis study was carried out to determine the incidence and predictors of anti-tuberculosis drug induced hepatotoxicity among TB/HIV co-infected patients at Jimma University Hospital, Ethiopia.Methods/Principal FindingsA nested case-control study was conducted by reviewing charts of all TB/HIV co-infected patients who commenced anti-TB treatment from January 2008 to December 2011 at Jimma University Hospital. Patients who had developed hepatotoxicity after at least 5 days of standard doses of anti-TB d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
27
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 22 publications
12
27
4
Order By: Relevance
“…The slow acetylation status has been shown to be the predominant phenotype in Ethiopian TB/HIV co‐infected patients . Patients with prior liver diseases and lower BMI (malnutrition) are also at higher risk of hepatotoxicity. Therefore, the combined effects of malnutrition, pre‐existing liver diseases and slow isoniazid acetylation status in some Ethiopian patients may have contributed to the severe drug‐induced hepatotoxicity that was a major cause of mortality in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slow acetylation status has been shown to be the predominant phenotype in Ethiopian TB/HIV co‐infected patients . Patients with prior liver diseases and lower BMI (malnutrition) are also at higher risk of hepatotoxicity. Therefore, the combined effects of malnutrition, pre‐existing liver diseases and slow isoniazid acetylation status in some Ethiopian patients may have contributed to the severe drug‐induced hepatotoxicity that was a major cause of mortality in our study.…”
Section: Resultsmentioning
confidence: 99%
“…43 This higher rate may be due to the growing use of polypharmacy in concomitant infectious and non-communicable diseases, a larger proportion of underweight patients with deranged pharmacokinetics and overlapping adverse effects of anti-TB and ART. 44,45 Alternatively, the variations in rates of fatal ADRs between studies and countries might be explained by differences in study design (prospective vs retrospective), disease distribution, drug therapy used and healthcare systems.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Age was divided into a younger age group (≤35 years of age) and older age group (>35 years of age) for the purpose of this analysis, based on previous studies [23,24]. Although it has been reported that advanced age can be a risk factor for anti-TB DIH [10,11], in the present study no correlation was found between age groups and the risk of developing anti-TB DIH (p=0.136). Also in other studies, advanced age was not a risk for anti-TB DIH [25,26].…”
Section: Discussionmentioning
confidence: 58%
“…Another study showed that 44 (44%) males and 56 (56%) females had anti-TB DIH [19]. A recent study by Alima et al (2013) reported 17 female patients (51.5%) who had anti-TB drug-induced hepatotoxicity and 53 (53.5%) among the control group [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation